Protocol for generating human CAR-engineered macrophages by Vpx-containing lentivirus - Yun Gao; Xiaobin Fang; Luo Zhang; Xiushan Yin (STAR Protocols)
Summary: Human-derived macrophages are notoriously difficult to infect with HIV-1-based lentiviruses, posing a limitation to the advancement of chimeric antigen receptor macrophage (CAR-M) therapy. Here, we present a protocol for generating human chimeric antigen receptor (CAR)-engineered macrophages using the viral protein Vpx (encoded by the Sooty Mangabey simian immunodeficiency virus [SIV] and HIV-2 lineages) incorporated into the lentivirus vector, which enhances infection efficiency. We describe steps for cell cultivation, lentivirus production, concentration, infection procedures, and efficiency assessments. This protocol provides a foundation to study macrophage manipulation, especially with CAR or other immune engagers.For complete details on the use and execution of this protocol, please refer to Gao et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.